Scrotal circunferenc, body weight, puberty and seminal characteristics in 1/2 Brahman x 1/4 Brown Swiss x 1/4 native crossbred young bulls - Madrid Bury, Ninoska; Noguera, Eduardo; Rincón, Ines; Zambrano, Sunny; García, Nestor; Canillo, Raul; Rincón, Rilma (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2013)
Scrotal circumference (SC), body weight (BW), age of puberty (P) and seminal characteristics were investigated in 19 1/2 Brahman x 1/4 Brown Swiss x 1/4 native crossbred young bulls. All bulls were evaluated at monthly intervals from 8 through 24 months of age. P, BW, and SC were 16.2Ó1.39 mo, 218.5Ó30.3 Kg and 23.5Ó 1.93 cm respectively. As age and BW increased SC increased (P < .01). The incidence of sperm abnormalities decreased (P < .01) as SC increased. The SC was correlated positively with age)(r= .92; P < .01), BW (r= .94; P <. 01) ejaculated volume (r=.55; (r=.69; P <. 0.1), sperm concentration (r=.54; P <. 01), progressive motility (r= .69; P <. 01) and % normal sperm (r= -.65; P <. 01) and negatively with % abnormal sperm (r= .65; P < .01).